Analisa Aspek Politik, Ekonomi, Sosial, dan Technology dalam Evaluasi Strategi Menangani Kebocoran Data Perusahaan - Hanun Hamidah (CV. Syntax Corporation Indonesia, 2021)
Tokopedia company engaged in digital is a unicorn-level start-up where users of the application application has numbered 100 million users, but in 2020 this company is dragged into conflict over the leaking of user data and sold by irresponsible parties dark websites. Then there are some aspects which are good name historical data of corporate users which is the political aspect which will be the Responsibility of the Company towards personal user data. The purpose of this study is to play a role of political, economic, social, and technological aspects in team strategy in its work strategy for better data companies. Which method in this study is descriptive research. The results in this study where there are still many people who have not application application, with the emergence of news what is this whether the social community remains for the application as it is to the marketplace to others. In addition, the complementary word strategy strategy is very amp.